ANALISIS PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOSIAL RESPONSIBILITY), DAN MANAJEMEN LABA TERHADAP AGRESVITAS PAJAK PERUSAHAAN DENGAN INSENTIVE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar Tahun 2015- 2019 di Bursa Efek Indonesia) - Hana Rohmatul Ulya; Sri Handayani (Diponegoro Journal of Accounting, 2021)
The purpose of this study is to analyze the effect arising from the characteristics of earning management, corporate social responsibility on tax aggressiveness with incentive as a moderating variable. The independent variable from this thesis, earning management measured through discretionary accrual and corporate social responsibility measured by CSR index. Tax aggressiveness as a dependent variable measured by ETR. This research uses incentive as moderating variable.Total sample in this study are 43 companies listed in Indonesia Stock Exchange during 2015- 2019. The sampling method used is purposive sampling method with predetermined criteria. This study uses multiple reggresion analysis to examine the effect of the characteristic of the earning management, corporate social responsibility on tax aggressiveness with incentive as a moderating variable.This study uses agency theory to formulate two hypotheses that lead to the results of the analysis. The results of this study indicate that the corporate social responsibility and earning management positively affects tax agresivenness and insentif could moderate. However, the earning management of the has no effect on tax aggressiveness.